Place names in Tuvan folkore; the case of heroic epics and folk songs - Ondar, Mengi V.; Koshkendey, Igor M.; Homushku, Chicagi O. (The New Research of Tuva, 2018)
The work reveals the patterns of toponyms functioning in the texts of Tuvan heroic epic, folk songs and ditties. The sources for the study were 38 texts of the Tuvan heroic epic, in which appeared 233 toponyms. Of song folklore, we used the lyrics of folk songs and ditties in the Tuvan language, both published and collected by the authors in their expeditions to Tuva, Mongolia, China; from these, more than 1,000 place names were selected. In general, place names in folklore are conventionally divided into two groups, with corresponding subgroups of the fictional and real toponymical objects. The names of fictional toponymical objects have been found to be used mostly in heroic tales. However, some texts of these tales contain the names of real toponymical objects, such as the hydronym Syt-Khөl. We have proved that the names of geographical objects used in the heroic epic are based on the mythological views of the people. Names of real geographical objects in Tuva have been found in folk songs and ditties. While in the heroic epic placenames act as guidelines in time and space, in ditties and folk songs they have an informative function, in addition to spatial semantics. In songs of praise, place names as the predicates are often made out by affixes of the first person and the accusative. Tuvans, by praising their homeland in their song folklore, expressed their personal attitude and sincere love to it, using place names in the lyrics of their songs, so we can assume that almost every corner of Tuva is praised. Thus, place names in folklore are not only a guideline in time and space, but also a way of representation of historical and cultural phenomena.